Chronic Mild Prenatal Stress Exacerbates the Allergen-Induced Airway Inflammation in Rats - Paulo J. Nogueira; Heloisa H. A. Ferreira; Edson Antunes; Nancy A. Teixeira (Mediators of Inflammation)
The effects of chronic mild prenatal stress on leukocyte infiltration into the airways was investigated in rat offspring. The chronic prenatal stress consisted of transitory and variable changes in the rat's living conditions. Offspring at adult age were actively sensitized (day 0) and intratracheally challenged (day 14) with ovalbumin. Bronchoalveolar lavage was performed in the offspring at 48 h after intratracheal challenge with ovalbumin. A significant increase in total leukocyte infiltration was observed in the nonstressed offspring group and this was associated with a marked recruitment of eosinophils without a significant effect on the influx of neutrophils and mononuclear cells. In the prenatal stressed offspring, the counts of both total leukocyte and eosinophils, as well as mononuclear cells, was increased by 50% compared to the non-stressed offspring. We provide here the first experimental evidence that chronic mild unpredictable prenatal stress produces a marked increase in the allergen-induced airway inflammation in the rat offspring.